Methanol in the RNA world: An astrochemical perspective - Mathew, Thomas; Esteves, Pierre Mothé; Prakash, G. K. Surya (Frontiers in Astronomy and Space Sciences, 2022)
The role and relevance of methanol in the origin and structure of the RNA world is discussed. Methanol is a pivotal, renewable, and regenerable source from which almost all chemical materials, simple or complex, can be accessed. Olefins and carbonyl compounds, amines and amino acids, peptides and polypeptides, and the molecular building blocks in the initial stages of the biological evolution to life’s origin are obtained through methanol as a source material by its chemical transformation. The formation of methanol, whether in stellar and interstellar media, in deep sea-bottom hot hydrothermal vents or from geothermal sources, results from CO2 hydrogenation. It is the basic reaction, setting the stage for the formation of fundamental “organic” building blocks for the formation of simple prebiotic cells to subsequent biological evolution to cells. The important observation of many organics– hydrocarbons and ions including the large expanse of methane and methanol in the interstellar medium and stellar peripheries is a clear indication of “stellar reductive processes” and ensuing reactions shedding light on the probable significant role of extraterrestrial methanol as the basic source material toward a multi-step transformation into complex life molecules such as RNA.